(3GdJPcQI GdaGNQI aj abg GdYJQI GdWGgQIs - (3TQa GdOjf GdMSjf Hf eMeO GdfMhjs
(3ChdgG (B:s
(3eHJhQ GdChd , jHOC GdehLhO efg CKfGA CQcGf GdhVhA , Hbhdg (B: (3GdQGHY GdeVeVI hGdESJfTGb HGOdc s
(3BNQgG (B:s
(3Gddge EfaYfG jG cQje HeG YdeJfG hCfTQ YdjfG SJQc Efc SejY GdOYGA Je cJGH GdJPcQI GdaGNQI s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG hCKfGAgG JYdjbGJ hTQhM cKjQI HNW eGdc GdfSNI SfI (B864(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3Gdabg GdESdGejs